Formação inicial dos professores com africanidades no processo de ensinar e aprender matemática no contexto escolar - Oliveira, Janaina Aparecida de (2020)
The research proposes a dialogue between a university and a public school during the Pedagogical Residency Program, which was developed for the initial training of undergraduate students of the Mathematics Graduation Course in the Africanities scenario in the process of teaching and learning mathematics in the school environment. In this process, sought to overcome obstacles arising from the implementation of Law no. 10.639 / 03, which instituted the obligation to teach Afro-Brazilian and African history and culture in Basic Education. The results were produced by the participant observation of the actions of undergraduate students in Mathematics Degree in a municipal public school in Uberlândia (MG), which was the field of execution of the sub-project Sciences of Nature / Mathematics of the Pedagogical Residency Program. Investigated some tasks produced collectively during the school year with the residents, and in particular some of their individual productions with Africanities and mathematics for students in the 9th grade of elementary school at the school studied. The productions of the investigative mathematics classes with Africanities were established with different didactic resources, making it possible to understand the impacts on the residents' subjectivity. Such productions allowed the participants to reflect on their educational practice and learn other knowledge, especially those related to Africanities and mathematics. The movement of teaching knowledge was also analyzed in view of the experiences lived in school and in investigative classes in the context of Africanities and mathematics, produced for the supervised internship of the undergraduate course in Mathematics. The results obtained revealed the importance of the development of collaborative work in the elaboration and execution of the tasks carried out with the students and also in the elaboration of the residents' productions, contributing to the production of knowledge and several other formative aspects within the theme. As a product, a digital book was developed in E-book format, with the projects and lesson plans of the activities carried out during the work, and which will be available to the teachers to assist them in educational practice, focusing on Africanities and mathematics.